Acquisition of land by the state under the shield of public trust doctrine: a critical analysis of sri lankan laws in its post – war context - Supasini, P. (University of Jaffna, 2019)
Public Trust Doctrine [PTD] intends to preserve certain natural and cultural resources for public use by the government and thus any use or sale of such land must be in the public interest. PTD used to be an effective tool of general application for citizens to obtain a judicial intervention to protect their rights, in its post-war situation in Sri Lanka; there are high degrees of statics shows that the private lands have been acquired by the government for the purpose of development without paying reasonable compensation. Hence, this paper intends to analyze to what extent the government can acquire the private land for such development by paying a reasonable compensation and the PTD aids the people to question the government for the acquisition. This paper is based on socio – legal study. It is a qualitative mode of approach; the data for this research was collected from Acts and International Conventions as a primary source and judicial decisions, text books, journals and scholarly articles available at both library and electronic data bases as a secondary source. This paper mainly focuses on the issues between freedom of the development of the country and Land rights of the people. Freedom of enjoyment of private property is the primary goal of the development, in practical situation human rights are violated in the name of the development. Even several years were lapsed from the end of civil war their issues are not addressed by the relevant authorities. This study aims to fill the space by proposing certain recommendations to settle the issues on Property Rights of the person and try to find to what extent the government can acquire the private land for the, economics of the country, Property Rights of individual, and strengthen the good governance with the sustainable development in Sri Lanka.
Keywords: Public trust doctrine; Land acquisition; Compensation; Land rights